Perkembangan Biji Dan Mutu Benih Beberapa Varietas Kedelai (Glycine max (L.) Merril) yang Diberi Pupuk P - Rio Supratman; Aslim Rasyad; Wardati ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Recently, fertilizer is considered as necessary cultural practices that could increase soybean production. So, this experiment was intended to determine the role of phosphorous fertilized on seed development and seed quality of several soybean varieties. Three varieties of soybean were grown in a plot of 3.2 by 3 m with planting density 40 x 15 cm. Ten days after planting, the plant were fertilized by mixing 53 kg Urea, 53 kg KCl and TSP as treatment applied. To obtained seed water concentration and seed dry weight, 300 flowers were randomly chosen from each plot, and 10 pods developed from the flowers were harvested every 5 days beginning from 15 days after anthesis (DAA) to 50 DAA. In addition to seed development, we observed dry matter accumulation rate, effective filling period, and seed quality at harvest. The change in seed moisture content was relatively fast from 15 DAA to about 45 DAA, then slightly slow until harvest time. Seed dry weight was very small until 20 DAA and contribute only 5 to 7% of its maximum dry weight. The linear increase in seed dry weight occurred from 20 DAA until 45 DAA, then tent to slow down before reaching physiological maturity. Application of P fertilizer increased KPBK and shortened WPE on Wilis and Gema but did not impact both traits on Gema. Grain yield of Kaba and Wilis was higher when fertilized by 25 kg P2O5 per ha, and tent to decline if fertilized by 50 kg P2O5 per ha. Key Words : seed water content, seed dry weight, P fertilizer, seed development